UTILIZATION OF ANGIOTENSIN-CONVERTING ENZYME INHIBITORS AND ANGIOTENSIN RECEPTOR BLOCKERS FOR GLAUCOMA - Gunawan, Alyssa Claudia Valerie; Ernawati, Titiek; Hendrawan, Kevin Anggakusuma; Khudrati, Wilson Christianto (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Glaucoma is a crucial ocular health issue that warrants meticulous attention according to its status as the leading cause of irreversible visual impairment on a global scale. The incidence of this illness has been on a steady rise, notably within the Asian region. Blood pressure impacts both intraocular pressure (IOP) and ocular perfusion pressure (OPP), which is the pressure responsible for facilitating blood flow to the eyeball. Hypertension is considered a contributing factor in the development of glaucoma. The Renin-Angiotensin-Aldosterone System (RAAS) plays a crucial role in the pathophysiology of hypertension and also contributes to the pathogenesis of glaucoma. The presence of Renin-angiotensin-aldosterone system (RAAS) inhibitors medications, such as angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin receptor blockers (ARB) have demonstrated efficacy in reducing intraocular pressure (IOP) and reducing ganglion cell apoptosis. Consequently, these pharmacological agents present a viable therapeutic approach to patients afflicted with hypertension and glaucoma.